The book of life - Gould, Stephen Jay. (New York : W.W. Norton, 2001)
Illustrations and text trace the history of evolution on Earth.
Includes bibliographical references and index.
Science Books & Films (A.A.A.S.).
Adult
Keywords: Evolution (Biology); Life -- Origin; Scientific illustration; Evolution (Biology); Life -- Origin; Scientific illustration